Respuesta :
[tex]\left\{\begin{array}{ccc}2x-y=8&(**)\\y=x-3&(*)\end{array}\right\\\\\text{Substitute }\ (*)\ \text{to}\ (**):\\\\2x-(x-3)=8\\2x-x-(-3)=8\\x+3=8\qquad\text{subtract 3 from both sides}\\\boxed{x=5}\\\\\text{Put the value of x to}\ (*):\\\\y=5-3\\\boxed{y=2}\\\\Answer:\ \boxed{a.\ (5,\ 2)}[/tex]
Answer:
Solution for the given system of equations is (5,2)
Step-by-step explanation:
We have been given the system of equations
[tex]2x-y=8....(1)\\y=x-3...(2)[/tex]
On substituting the value of y from equation (2) in equation (1)
[tex]2x-(x-3)=8[/tex]
Now, we solve the equation for x
[tex]2x-x+3=8\\x+3=8\\x=5[/tex]
Substituting the value of x in equation (2)
[tex]y=5-3\\y=2[/tex]
Therefore, the solution for the given system of equations is (5,2)
a is the correct option.